Inbound and Outbound Tourism in China: A Perspective Article - Dávid, Lóránt Dénes; Archi, Youssef El; Zhu, Kai; Varga, Imre; Benbba, Brahim; Csizmadia, Norbert (International Journal of Engineering and Management Sciences, 2024)
The tourism industry in China has undergone significant changes due to globalization, technology, and changing consumer preferences. This perspective article, based on a systematic literature review, examines examines trends, challenges, and opportunities in inbound and outbound tourism in China, focusing on the industry's dynamism. Both inbound and outbound tourism have been negatively impacted by the COVID-19 pandemic, which has prompted new strategies and environmental adaptations. China has changed its priorities within the country to encourage domestic travel and support local firms. The rise in internationalisation and the growing middle class in China have led to an unprecedented rise in outbound travel. Chinese travellers are affecting travel habits and spending all around the world in the tourism sector. Language barriers, cultural differences, and safety concerns are some of the challenges that come with travelling abroad. To reach its full potential, China needs to adapt to the shifting global environment and take into account the specifications and preferences of both inbound and outgoing tourists.